"It's dry, it has fewer charms!": Do perceptions and values of intermittent rivers interact with their management?. Issue 139 (January 2023) - Cottet, Marylise; Robert, Agathe; Tronchère-Cottet, Hervé; Datry, Thibault
Abstract: Intermittent rivers, which do not flow all year round, have biophysical functioning specificities which need to be considered when defining management policies, even more so in the current context of global change. However, in Europe intermittent rivers benefit from the same regulations as permanent rivers, which undoubtedly leads to their degradation. This paper aims to identify (1) how perceptions and values of intermittent rivers interact with their management and (2) determine whether the prospect of climate change leads the stakeholders to questioning their perceptions and values of intermittent rivers and the way we should manage them. Semi-structured interviews and mental mapping exercises were conducted with 28 various stakeholders (elected officials, fishers, river managers, and residents), all of whom lived along the French intermittent Albarine River. Qualitative analysis of the discourses and maps confirms strong interactions between the perceptions and values related to intermittent rivers and their management. The results highlight social devaluation of the intermittent section in terms of aesthetics, recreation, and biological values. They also point to the role of power plays between river managers and fishers, in the prioritization of management actions that favor perennial sections to the detriment of intermittent ones. These dynamics of devaluing and discarding intermittent sections or rivers from management plans are all the more alarming as there is little propensity among river stakeholders to think about the future of these intermittent rivers and their value in the context of climate change, where the prevalence of intermittent rivers is likely to increase dramatically. Highlights: Stakeholders devalue intermittent rivers (IR) compared to perennial rivers. Devaluation is due to aesthetic, recreational and biological reasons. Devaluation leads to IR or IR sections being excluded from management plans. Stakeholders do not consider a future with increased intermittency with climate change.